1991
DOI: 10.1111/j.1365-3024.1991.tb00545.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of mice and baboons with the recombinant Sm28GST affects both worm viability and fecundity after experimental infection with Schistosoma mansoni

Abstract: A member of the glutathione S-transferase family, Sm28GST has previously demonstrated a good ability to protect rodents against experimental infection with Schistosoma mansoni. In order to evaluate its efficacy in a model closer to man, two different protocols of immunization with recombinant Sm28GST were tested on baboons in a large-scale trial. Three injections in the presence of aluminium hydroxide as adjuvant resulted in a significant 38% reduction in the adult worm burden together with a trend for a lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
79
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(82 citation statements)
references
References 32 publications
1
79
0
1
Order By: Relevance
“…Recently it has been demonstrated that IgA antibody to a 28-KD glutathione-s-transferase of S. mansoni seemed to play a protective role in patients with schistosomiasis, limiting egg laying and hatching (Grzych et al 1993) and reducing the pathology related to the formation of egg granulomas (Boulanger et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been demonstrated that IgA antibody to a 28-KD glutathione-s-transferase of S. mansoni seemed to play a protective role in patients with schistosomiasis, limiting egg laying and hatching (Grzych et al 1993) and reducing the pathology related to the formation of egg granulomas (Boulanger et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Sm28GST also represents a major antigen of S. munsoizi. Immunization with recombinant Sm28GST generated partial protection to infection in rodents and monkeys (Balloul et al, 1987;Boulanger et al, 1991). Even though the mechanisms by which anti-Sm28GST antibodies protect against infection still remain to be defined, the presence of antibodies blocking the Sm28GST activity was positively correlated with the reduction of female fecundity and egg viability in vitro and in vivo (Xu et al, 1991(Xu et al, , 1993.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme displays limited structural similarity and enzymatic activities characteristic of a, p, and TC class GST enzymes (Walker et al, 1993). Sm28GST was also shown to be a major parasite antigen; immunisation with the purified or recombinant enzyme induced protection against infection in different experimental models (Balloul et al, 1987a;Boulanger et al, 1991). Very little is known about the regulation of the expression of this enzyme.…”
mentioning
confidence: 99%
“…Sm28-GST is expressed in the sub-tegumental tissues of the parasite and vaccination studies in rats and hamsters with the S. haematobium equivalent [55] indicated its significant protective potential. Trials in primates demonstrated an anti-fecundity effect [56]. Clinical testing of Sh28-GST in people showed that the vaccine was immunogenic and antibody inhibited the enzymatic activity of the recombinant protein [57].…”
Section: Schistosomiasismentioning
confidence: 99%